Evaluation of Load Capacity of Stratified Soils (2 Layers) by Means of Numerical Analytical Comparison - Quintero-Chamorro, Jairo Alejandro; Martínez-Ortega, Brayan Julián; Cruz-Velasco, Lucio Gerardo (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The methods for determining load capacity in stratified soils are numerous and differ in their methods and results. These differences in analysis lead to uncertainty in engineering practices or over-dimensioning of the foundation solution. This study seeks to determine three analytical methods of load capacity in stratified soils (2 layers) for shallow foundations: 1) Imaginary foundation, 2) Average parameter method (APM), and 3) Terzaghi's method to compare their results with those obtained from numerical modeling by means of the finite element method using a widely applied software (Abaqus academic version). Within the methodology developed in the finite element modeling, variables were parameterized (modulus of elasticity, depth of deflection, and displacement-load) and two behavioral laws were evaluated (Elastic and Drucker-Prager). The results that were obtained from the analysis show that when performing numerical modeling using the law of elastic behavior in soils of two layers, exaggerated results are generated with respect to analytical methods. Another important result is that when hard soils are on top of soft soils the results of numerical and analytical methods tend to be similar to each other. Most importantly, the variables that have the greatest influence on the load capacity in soils of one and two layers are the angle of friction, yield stress, and in the case of numerical analysis the constraint displacement (load). In addition, it was observed that for numerical modeling better results are obtained when considering an elastoplastic model, such as Drucker Prager.